Given:
The expression is [tex]10 - (-6)[/tex].
Sam's calculation is [tex]10 - (-6) = 10 + (-6) = 4[/tex]
To find:
Whether Sam's thinking correct or not.
Solution:
We have,
[tex]10 - (-6) = 10+6[/tex] [tex][\because (-)(-)=(+)][/tex]
[tex]10 - (-6) = 16[/tex]
[tex]10 - (-6) \neq 4[/tex]
Therefore, Sam's thinking was incorrect.
On number first we have to move 10 units from 0 in positive direction after that negative sign means move in left direction.
But we have 2 negative signs so we need to move 6 units more on positive or right direct as shown below.